Integrals of certain random functions with respect to general random measures - Radchenko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For random functions that are sums of random functional series, we determine an integral over a general random measure and prove limit theorems for this integral. We consider the solution of an integral equation with respect to an unknown random measure.